Evaluation Of Platelet Indices as A Diagnostic Tool for Early Diagnosis of Neonatal Sepsis - Haque, Eahsanul; Kumar Singh, Rajesh; Shruti, Shruti (Journal of Neonatal Surgery, 2025)
Neonatal sepsis remains a leading cause of morbidity and mortality, particularly in low- and middle-income countries. Early and accurate diagnosis is essential to initiate prompt treatment. Platelet indices have emerged as accessible and cost-effective markers for the early detection of sepsis in neonates. To evaluate the diagnostic utility of platelet count (PC), mean platelet volume (MPV), and platelet distribution width (PDW) in the early identification of neonatal sepsis. This randomized prospective study was conducted over 18 months (2023–2025) in the Neonatal Division of the Department of Paediatrics and the Department of Haematology at the Integral Institute of Medical Sciences and Research, Lucknow. A total of 200 neonates were enrolled, including 100 with suspected or confirmed sepsis (cases) and 100 age-matched healthy neonates (controls). All participants underwent clinical examination and laboratory investigations, including complete blood count, C-reactive protein (CRP), platelet indices (PC, MPV, PDW), and blood culture. Statistical analysis was performed using SPSS version 20.0. Septic neonates exhibited significantly higher rates of fever (94% vs. 44%), respiratory distress (89% vs. 58%), and feeding intolerance (88% vs. 48%) compared to controls (p < 0.0001). Thrombocytopenia (1.5 lakh/µL) was observed in 86% of cases and 24% of controls. Elevated MPV (>10.8 fL) and PDW (>19.1) were significantly associated with sepsis (p < 0.0001). Platelet count alone showed 86% sensitivity and 76% specificity. When PC, MPV, and PDW were combined, specificity improved to 83.9%, with an overall diagnostic accuracy of 81.3%. Platelet indices, particularly when assessed together, offer valuable support in the early diagnosis of neonatal sepsis. Their routine availability and affordability make them suitable for integration into standard sepsis screening protocols